DIGITAL CORRELATION OF SOIL MUNSELL COLOUR AND COMPARE IT WITH DIGITAL IMAGE CLASSIFICATION FOR DIFFERENT SAMPLES OF SOIL USING CLASSIFICATION PROGRAM - Taha Abdul Hadi Taha Dawood Al-jawwadi (Mesopotamia Journal of Agriculture)
The research depended on reading soil color by using Munsell soil color chart for Twenty four soil samples with two duplicates. The soil samples were collected from three Iraqi governorate containing four samples of soil storm sediments that blowing on the town in different times. Then re-reading the same sample in same last optical way but in digital method, and performing some image enhancement like cutting, resizing, reading image on digital Munsell soil color on the computer screen after fix and punching the Munsell soil color page in usual program, then reading the value of soil and Munsell soil color as reflective to check the optical recognize accuracy and harmony soil surface. The study referred to the sameness and converges of most samples with usual optical reading of real Munsell soil color, so we can depend on it in case of the absence of papering Munsell soil color.